Analysis of mathematical investigation ability reviewed from personality types in Junior High School - Caesarla Elintang Yolawati; Sri Subarinah; Amrullah Amrullah; Nyoman Sridana (Jurnal Pijar Mipa, 2022)
Mathematical investigative ability is one of the skills that need to be honed in every student to improve problem-solving skills and develop thinking skills. A mathematical investigation has four stages: specialization, conjecture, justification, and generalization. This paper aims to describe the mathematical investigative abilities of extroverted and introverted personality students. This study was conducted qualitatively on Junior High School 1 Mataram students in grades IX-F, selected by a simple random sampling technique. Based on the mathematical investigation test results and personality type, 6 students were selected to be interviewed. The results showed that extrovert students were alert, independent, and outward-looking or oriented when doing mathematical investigation tests, such as directly working on questions deftly and trying out their ideas. Therefore, students with extrovert personalities mostly succeeded in going through three stages of an investigation, namely: specialization, conjecture, and justification. Introvert personality students, when doing mathematical investigations, are thorough, detailed, focused, and think deeply, such as checking answers by doing one more time, then rereading the answers in detail, and focusing on thinking deeply at the generalization stage. Therefore, most introverted students passed three stages of mathematical investigation: specialization, conjecture, and justification. However, some introverted students also made it through the fourth stage.